JMP version 12 : discovering JMP (JMP, a business unit of SAS, 2015)
" ... Provides a basic introduction to using JMP. For new users of JMP, this is a great place to start. The book also includes details about importing your data into JMP, analyzing the data, and sharing the results."--
"12.1.". - Includes index. - Online resource; title from PDF title page (Ebsco, viewed July 20, 2015)
Keywords: JMP (Computer file); Mathematical statistics -- Data processing; Information visualization; Statistique mathématique; Informatique; Visualisation de l'information; MATHEMATICS; Applied; MATHEMATICS; Probability & Statistics; General; Mathematical statistics; Data processing